2000
DOI: 10.1046/j.1442-200x.2000.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular energetics in Fontan circulation: Evaluation with a theoretical model

Abstract: Thus, it was inferred that Fontan circulation had intrinsic disadvantages and this may explain, in part, abnormal functional status and decline in survival following this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
(43 reference statements)
5
17
0
Order By: Relevance
“…The sensitivity of CVP to increase in RTCPC was 0.64, implying that a 10% increase in resistance results in a 6.4% increase in CVP. The increase in CVP in the SV has been previously shown using acute in vivo animal experiments (40), human experiments (35), and theoretical experiments (14,22). However, the impact of the TCPC procedure on CVP was shown for the first time in this study.…”
Section: Lumped Parameter Model Validationsupporting
confidence: 42%
See 3 more Smart Citations
“…The sensitivity of CVP to increase in RTCPC was 0.64, implying that a 10% increase in resistance results in a 6.4% increase in CVP. The increase in CVP in the SV has been previously shown using acute in vivo animal experiments (40), human experiments (35), and theoretical experiments (14,22). However, the impact of the TCPC procedure on CVP was shown for the first time in this study.…”
Section: Lumped Parameter Model Validationsupporting
confidence: 42%
“…Pressure-volume loops were used to evaluate the slope of the end-systolic volume elastance, or E es, and the vascular Ea property. These parameters were evaluated based on the methodology outlined by Nogaki et al (22). All authors had full access to the data and take responsibility for its integrity.…”
Section: Modeling Rest/exercise Conditions and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The other coupling studies in Fontan patients used similar methods as ours or even much simplified, less‐rigorous methods, but did not include similarly studied non‐Fontan patients to determine whether VA parameters were abnormal relative to persons without Fontan circulation 30, 31. A mathematical simulation study and an animal study of acute Fontan physiology indicated that immediately after creation of a Fontan circulation, Ees is mildly reduced whereas Ea is increased 24, 32. In contrast, chronically, in adult Fontan patients, we found that contractility was significantly decreased as assessed by multiple load‐insensitive measures of ventricular contractility (Ees, PRSW, and PPI) whereas Ea was similar to age, sex, and body size matched controls without CHD.…”
Section: Discussionmentioning
confidence: 99%